Edukasi Cara Pengolahan Sediaan Herbal Untuk Hipertensi di Kampung Ketupat RT. 07 Kota Banjarmasin - Pebrianti Pebrianti; Zahra Desy Safitri; Michael Elisier; Nawwal Nawwal; Nur Syifa; Ani Agustina; Rohama Rohama (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2026)
The rapid advancement of science and technology in pharmaceutical preparations has not entirely shifted public preference toward modern medicine. This is evident from the fact that many community groups continue to use herbal plants as alternative therapeutic options, although their knowledge regarding appropriate use remains limited. This community engagement program aimed to improve residents' knowledge and skills in Kampung Ketupat RT. 07, Banjarmasin City, in the utilization of herbal plants as antihypertensive agents. The program consisted of three phases: the preparation phase (survey and material development), the implementation phase (education and a workshop on celery juice preparation), and the evaluation phase, which involved comparing pre-test and post-test results. Educational activities were conducted in person using leaflets as learning media. The results showed an improvement in participants’ knowledge, as indicated by an increase in the number of participants with good knowledge levels—from 4 (26.67%) before the intervention (pre-test) to 10 (66.67%) after the educational session (post-test).